Self Assessment of Summaries Facilitated by Padlet to Improve Reading Comprehension Skills - Aguilar Chalacán, Maricela (2021)
This innovation, “Self assessment of Summaries Facilitated by Padlet to Improve Reading Comprehension Skills,” pretends to help 10th-grade students of the public school “Leopoldo Mercado” located in Quito, who are in A1 level of English proficiency. The aim of this study is to improve reading comprehension through summaries, using self assessment to motivate students to monitor and reflect on their learning, raise awareness of their progress, and foster critical thinking skills.